Morphine Plus Bupivacaine Vs. Morphine Peridural Analgesia in Abdominal Surgery: The Effects on Postoperative Course in Major Hepatobiliary Surgery. Issue 6 (2000) - Barzoi, G.; Carluccio, S.; Bianchi, B.; Vassia, S.; Colucci, G.; Mangiante, G. L.
Abstract : Anaesthesia and surgical procedures lead to a reduction of intestinal motility, and opioids may produce a postoperative ileus, that might delay postoperative feeding. The aim of this prospective randomised study is to test whether or not different kinds of epidural analgesia (Group A: morphine 0.00 17 mg/kg/h and bupivacaine 0.125% – 0.058 mg/kg/h; Group B: morphine alone 0.035mg/kg/12h in the postoperative period) allow earlier postoperative enteral feeding, enhance intestinal motility a passage of flatus and help avoid complications, such as nausea, vomiting, ileus, diarrhoea, pneumonia or other infective diseases. We included in the study 60 patients (28 males and 32 females) with a mean age of 61.2 years (range 50–70) and with an ASA score of 2 or 3. All patients had hepato–biliary-pancreatic neoplasm and were candidates for major surgery. We compared two different pharmacological approaches, i.e., morphine plus bupivacaine (30 patients, Group A) versus morphine alone (30 patients, Group B). Each medication was administered by means of a thoracic epidural catheter for the control of postoperative pain. In the postoperative course we recorded every 6 hours peristaltic activity. We also noted morbidity (pneumonia, wound sepsis) and mortality. Effective peristalsis was present in all patients in Group A within the first six postoperative hours; in Group B, after 30 hours. Six patients in Group A had bowel motions in the first postoperative day, 11 in the second day, 10 in the third day and 3 in fourth day, while in Group B none in the first day, two in the second, 7 in the third, 15 in the fourth, and 6 in the fifth: the difference between the two groups was significant ( P <0.05 in 1st, 2nd, 4th and 5th days). Pneumonia occurred in 2 patients of Group A, and in 10 of Group B ( P <0.05). We conclude that epidural analgesia with morphine plus bupivacaine allowed a move rapid return to normal gut activity and early enteral nutrition compared with epidural analgesia with morphine alone.